The interplay of economics, education, and management in shaping consumer choices - Sebullen, Michael Tomas; Özker, Ahmet Niyazi; Donmez, Cem Cagri; Owusu, Rebecca; Balder, Nazdar; Al Souleiman, Habib; Musa, Haslinda (Association for Consumer Research, 2025)
Consumer decision-making is shaped by multiple interacting factors that reflect financial capacity, educational exposure, and brand-related managerial influences. Using a real consumer dataset, the study investigates how these dimensions jointly contribute to variations in purchasing engagement, campaign responsiveness, and spending behavior. Descriptive and correlational analyses reveal substantial heterogeneity in consumer behavior, with income displaying a strong positive association with total expenditure, purchasing frequency, and the overall Consumer Choice Index (CCI). Regression findings further confirm income as the most influential predictor of consumer choice, while browsing intensity through web visits shows a significant negative effect, suggesting that information search does not necessarily result in purchasing action. Education demonstrates a small positive but statistically non-significant influence, consistent with its limited predictive role in the model. Managerial indicators such as recency and complaints also show non-significant associations, whereas campaign acceptance contributes positively at the descriptive level as a behavioral component of CCI. Overall, the findings highlight the multidimensional nature of consumer choice and underscore the need for integrated models that capture economic, cognitive, and managerial determinants simultaneously. The results offer meaningful implications for marketers, policymakers, and educators seeking to enhance consumer empowerment and optimize engagement strategies in increasingly competitive and digitally mediated marketplaces.